RETRACTED: The Nexus between sustainability of business model innovation, financial knowledge, and environment: A developing economy perspective - Yun, Xiaopeng; Zhang, Jie; Ali, Anis; Khurram, Haris (Frontiers in Environmental Science, 2022)
This study intends to investigate how aspects such as financial knowledge and the rate of technological advancement influence the lifetime of enterprises in developing nations like Pakistan. For this purpose, a survey study was designed to obtain data from 325 business owners in different parts of the country. Structural Equation Modelling (SEM) was utilized to analyze this dataset. According to the analysis outcomes, not only do practices connected to financial literacy and innovation play a crucial role in a firm's long-term viability, but they also have a substantial beneficial impact on the company's viability. The research concluded that an increase in financial knowledge, expertise, and experience in corporate operations helps the continued viability of firms. Knowledge of financial concerns also predicted the company's ability to innovate and adapt. In addition to the environmental sustainability of the business. As a result, it was concluded that it plays the role of a mediator in the link between innovation and the ongoing existence of businesses. Because of this, financial literacy is now acknowledged as a vital knowledge resource for determining one's financial course of action, which was not the case previously. According to the study's conclusions, for businesses to continue to be sustainable, authorities need to enhance their financial literacy level and adopt sustainability models into their day-to-day operations.